AquaPath: a web-based user interface for rapid identification of aquaculture pathogens based on long-read DNA sequence data - CGIAR Platform for Big Data in Agriculture (2021)
Currently AquaPath features three identification tools that cover (1) major sequence type of piscine Group B Streptococcus (GBS), (2) most serotype of GBS and (3) major biotype of Yersinia ruckeri. AquaPath is still under development and more tools will be developed to cover additional bacterial species. https://worldfishcenter.github.io/rappseq/identify/